Reconstruction of Communicative Rationality: A Study on the Digital Mass Media Society in Indonesia - Ribut Priadi; Muhammad Thariq (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
This study examined the cognitive response of Indonesian society (namely, the people who use digital mass media) to the narratives built by digital mass media. Establishing an argumentative “communication” relationship between digital mass media and society is necessary because the narratives built by digital mass media tend to represent particular interests. Therefore, between the two, an argumentative “communication” relationship is needed to reach a consensus through the expression of rational language. This relationship actually forms a communicative society based on the value of emancipatory critical rationality to achieve "consensus". Thus, the problem posed in this study, ‘How is the cognitive response and form of digital society in Indonesia within the scope of the digital mass media era?’ To answer that question this study used a qualitative approach by conducting a sociological study of the narratives in the digital mass media user community, especially convergence mass media (kompas.com, tempo.co, and tribunnews.com). While the technique of the validity test of the narrative data of people who use digital mass media uses was the triangulation technique of sources and theories. This study found that digital society can create and produce imaginative spaces based on its own laws and culture. Its awareness of the digital mass media narrative is solid and shifts its passive role as an object to be ‘interactive’ (itself as a subject) with mass media. Meanwhile, the relationship between digital society and communication technology has three options, namely, first, digital society positions itself as technology; second, humanize technology as itself; and third, dialectically compromising the potential of humanity and technology.